A JURIDICAL AND PHILOSOPHICAL ANALYSIS OF A NEW INSTITUTIONAL FRAMEWORK TO REPLACE SKK MIGAS IN THE IMPLEMENTATION OF ARTICLE 33 OF THE 1945 CONSTITUTION AND RENEWABLE ENERGY - Rizkiyadi Darmowiyoto; Ratna Januarita (RADJA PUBLIKA, 2025)
The oil and gas (Migas) sector holds a strategic role in Indonesia’s economy, serving both as a significant source of state revenue and as the country’s primary energy supply. However, national oil and gas governance continues to face major challenges, particularly regarding institutional arrangements and the effectiveness of existing supervisory mechanisms. The Constitutional Court (Mahkamah Konstitusi) Decision No. 36/PUU-X/2012 (“MK Decision No. 36”) which dissolved the Executive Agency for Upstream Oil and Gas Business Activities (BP Migas), reaffirmed the need for the establishment of a new institution that is more in line with the mandate of Article 33 of the 1945 Constitution of the Republic of Indonesia. To date, the Special Task Force for Upstream Oil and Gas Business Activities (SKK Migas), which replaced BP Migas, remains a provisional entity without a permanent statutory basis. This study aims to conduct a juridical and philosophical analysis of the potential form of a new institutional framework to replace SKK Migas. It adopts an approach grounded in economic law theories, including the Economic Efficiency Theory of Richard A. Posner, the Pure Theory of Law by Hans Kelsen, the Theory of Distributive Justice by John Rawls, John Austin’s Theory of Legal Validity, The Concept of Law of H.L.A. Hart, and other relevant legal theories. Through this theoretical lens, the research explores institutional models that are more effective, efficient, transparent, accountable, and oriented toward public welfare in the governance of the national oil and gas sector. The findings indicate: (1) The draft of Oil and Gas Law (RUU Migas) must stipulate a legally stronger institutional framework that integrates both supervisory and operational functions through transparent and accountable mechanisms; (2) The draft legislation should incorporate the principles of renewable energy (EBT) and the Sustainable Development Goals (SDGs), while remaining grounded in the mandate of Article 33 paragraphs (2) and (3) of the 1945 Constitution as the foundation of the State. Accordingly, this study recommends that oil and gas regulation should not only focus on enhancing investment but also promote transparency, accountability, and energy sustainability—ensuring that national oil and gas policy aligns with the constitutional mandate of Article 33 and international standards in support of a sustainable energy transition.